THE INFLUENCE OF LEARNING STRATEGIES AND CONFIDENCE ON BASKETBALL DRIBBLE LEARNING OUTCOMES - Permana, Indra (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Abstract Interdisciplinary approaches to understanding the factors that influence basketball dribble learning are also relevant. Psychological factors such as motivation, perception of self-esteem, and coping strategies in the face of failure can also influence player learning outcomes. Thus, this research not only explores the technical aspects of learning, but also expands our view of the psychological dynamics involved in the learning process of sports skills. Basketball Dribble is one of the demands in the learning process of PJOK in High School. In the process of learning of course each student has different skills – different. In this case, PJOK teachers are charged with using learning strategies that make it possible to match students. This research is a 2×2 factorial design experiment because it consists of two factors and each factor has two levels. The aim of this study was to determine whether the two learning strategies, the Inkuiri Learning Strategy (SPI) and the Problem-Based Learning Strategies (SPBM), had a greater influence on Dtibble basketball learning outcomes.